2008
DOI: 10.2174/1874354400802010023
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Past Oppositional Defiant Disorder in Adults with Attention-Deficit/Hyperactivity Disorder~!2008-09-19~!2008-10-22~!2008-11-28~!

Abstract: Abstract:Objective: While DSM-IV Attention-deficit/hyperactivity disorder (ADHD) comorbid with antisocial behaviours identified by DSM-IV conduct disorder (CD) has been claimed as a 'distinct subtype', there is less information about the validity of a subtype based on the more prevalent comorbidity of oppositional defiant disorder (ODD). The present study investigated the associations of past ODD with past and recent psychopathology in adults with ADHD.Methods: 94 clinic-referred adults (73 male; 21 female) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The mean ADSA total score indicated ‘very considerable problems’ related to ADHD (33). Various aspects of the present methodology have been discussed previously (30–32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean ADSA total score indicated ‘very considerable problems’ related to ADHD (33). Various aspects of the present methodology have been discussed previously (30–32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found associations of these covariables with aggression and/or ADHD. A history of past ODD, and to a lesser extent past CD, both of which incorporate aspects of aggression, have been reported to be associated with features of adult ADHD (32), verbal IQ has been negatively correlated with aggression in various male samples (38, 39) and features of ADHD have been reported to diminish with increasing age (1). Also, as increased aggression has been associated with comorbidity in ADHD samples (23, 24), the range of comorbidity reflected by ‘PD features’ and GSI were also selected as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation